Mandibular chondroblastic type osteosarcoma primarily diagnosed as chondrosarcoma as a result of radiation therapy: a case report - Rone, Alise Elizabete; Bāgante, Ieva; Vasiļčenko, Irina; Zariņš, Jānis; Deksnis, Renārs; Hasnere, Sigita (International Journal of Scientific Reports, 2025)
Radiation therapy is a recognized etiological factor for osteomyelitis, osteoradionecrosis and multiple sarcomas such as chondrosarcoma and osteosarcoma. Here we present a case of mandibular chondroblastic type osteosarcoma induced by radiotherapy which was primarily misdiagnosed as chondrosarcoma. A female presented with main complaint of pain at the extraction site following multiple teeth extraction and sequestrectomy on the right lower jaw. Medical history revealed stage IV squamous cell carcinoma of the base of the tongue which was treated by surgical excision, chemotherapy and radiotherapy ten years ago. Four recurring sequestrectomies were performed, but only histological material from the fourth sequestrectomy revealed grade 2 chondrosarcoma. This was followed by resection of the tumour and floor of the mouth, mandibular, lip and facial skin reconstruction and operation material through histology was again confirmed to be grade 2 chondrosarcomas. In a year’s time, pathological nodule in thyroid gland was found on CT, surgery was performed. Operation material now revealed high grade chondroblastic type osteosarcoma and additional radiotherapy and chemotherapy was prescribed. This case illustrated chondrosarcoma and chondroblastic type osteosarcoma as a rare malignant incidence, with diagnostical difficulties and treatment. Differential diagnosis should be considered if no positive changes are observed after the designated therapy as well as importance of immuno histological evaluation. One treated malignancy does not exclude development of another unrelated malignancy.